Factors influencing the community in Shah Alam to trust zakat institutions / Nur Ellina Alia Salehuddin - Salehuddin, Nur Ellina Alia (Faculty of Business and Management, 2019)
Zakat is the third pillars in Islam and it is an obligation for Muslims to pay zakat. It can be defined as a system that can lessen poverty with the purpose of reducing the gap between the poor and the rich. The zakat collection will be used to distribute to the eligible recipients of zakat. Since zakat involve a large number of individuals, an authority, institutions or management is needed to manage the zakat collection. The authority is given the trust by Muslims in collecting and distributing the zakat collection according to sharia. The trust of zakat payers has helped the survival of zakat institutions as well as in increasing collection of zakat fund. This study aims to figure out the factors influencing the zakat payers to trust zakat institutions in Shah Alam. This paper provides a brief explanation on zakat, the factors that influence the zakat payers to trust zakat institutions, how the research methodology is used and the findings of the study. The important contribution of this study is that those factors identified could be useful in planning or strategizing in increasing participation of zakat in the future.